2000
DOI: 10.1097/00002030-200009080-00019
|View full text |Cite
|
Sign up to set email alerts
|

Religion and protective behaviours towards AIDS in rural Senegal

Abstract: These findings stress the need to intensify the involvement of religious authorities in HIV/STD prevention at the local level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 5 publications
3
45
1
1
Order By: Relevance
“…It is unclear whether this lower risk perception was related to a lower number of risk taking behaviors or if they felt "protected" by their faith. However, in the same study, women who considered their religion to be important to them had a statistically significant higher perception of risk than other women 6 . The effect of religion on sexual partnerships may vary depending on the religion and the level of religiosity of the individual, as well as the various religions represented and religiosity obser ved at a community level, which varies significantly within regions, countries, and communities.…”
Section: Social Demographic and Economic Determinants Of Risky And Pmentioning
confidence: 72%
See 2 more Smart Citations
“…It is unclear whether this lower risk perception was related to a lower number of risk taking behaviors or if they felt "protected" by their faith. However, in the same study, women who considered their religion to be important to them had a statistically significant higher perception of risk than other women 6 . The effect of religion on sexual partnerships may vary depending on the religion and the level of religiosity of the individual, as well as the various religions represented and religiosity obser ved at a community level, which varies significantly within regions, countries, and communities.…”
Section: Social Demographic and Economic Determinants Of Risky And Pmentioning
confidence: 72%
“…Many studies in the past decade have examined the association between various individual and community level factors and HIV infection and prevalence in various sub-Saharan African settings [4][5][6][7][8] . Underlying these studies is the association between sociodemographic and economic factors, such as age, age at first intercourse, religion, occupation, mobility, education, and socioeconomic status, and various risky or protective sexual behaviors.…”
Section: Social Demographic and Economic Determinants Of Risky And Pmentioning
confidence: 99%
See 1 more Smart Citation
“…In these researches, several religiously motivated behaviors such as higher rates of uncircumcision, fewer instances of extramarital sexual intercourse, and reduced consumption of alcohol were some of the factors that favour HIV prevention. These factors led to lower HIV prevalence rates among Muslims [3][4][5][6]. Further studies with Catholic Church and some Pentecostals showed that religious beliefs do not correlate with HIV protective behaviors [7].…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, also suggestions that religious ''faith-based'' organisations and religious leaders may play a positive role in combating the spread of HIV (see, e.g. UNICEF, 2003;Lagarde, Enel, Seck, Gueye-Ndiaye, Piau, Pison et al, 2000;Odiwuor, 2000, p. 115). With this article, I hope to contribute with some input into this discussion.…”
Section: Introductionmentioning
confidence: 99%